2012
DOI: 10.1063/1.4730611
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial doping induced superconductivity at 15.3 K in Nb5Ge3 compound

Abstract: It is reported superconductivity in Nb5Ge3C0.3, an interstitial carbide compound. The temperature dependence of the electrical resistivity, ac-susceptibility, and heat capacity (HC) indicate that a bulk type-II superconductivity appears at TC = 15.3 K. Magneto-resistance measurements suggest an upper critical field of BC2 ∼ 10.6 T and a coherence length of ξ ∼ 55 Å at zero temperature. Neutron diffraction analyzes locate the carbon atoms at the interstitial 2b site of the Mn5Si3 type-structure. Heat capacity d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…Likewise, T C of Zr 5 Sb 3 decreases with the addition of oxygen until the supresison of the superconducting phase in Zr 5 Sb 3 O [18]. The highest reported T C in this family, however, belongs to Nb 5 Ge 3 C 0.3 [23], with T C = 15.3 K. Recently, Renosto et al reported a comprehensive study of the effects of carbon doping on the superconducting properties of Zr 5 Pt 3 C x [25]. It was found that T C first increases from 6 K (x = 0) to 7 K (x = 0.3) and further decreases monotonously for x > 0.3 [25].…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Likewise, T C of Zr 5 Sb 3 decreases with the addition of oxygen until the supresison of the superconducting phase in Zr 5 Sb 3 O [18]. The highest reported T C in this family, however, belongs to Nb 5 Ge 3 C 0.3 [23], with T C = 15.3 K. Recently, Renosto et al reported a comprehensive study of the effects of carbon doping on the superconducting properties of Zr 5 Pt 3 C x [25]. It was found that T C first increases from 6 K (x = 0) to 7 K (x = 0.3) and further decreases monotonously for x > 0.3 [25].…”
Section: Introductionmentioning
confidence: 78%
“…When combined with superconductors, topological materials could also harbor Majorana quasiparticles with non-Abelian exchange statistics, thus possibly opening the way for the quantum computation era [16]. In this context, a large number of intermetallic compounds with general formula M 5 X 3 (M is either a transition or rare earth metal and X is a metalloid) represent a novel platform to explore a plethora of unique properties [17][18][19][20][21][22][23][24][25][26]. These compounds can crystallize in three different prototypes: (i) orthorhombic Yb 5 Sb 3 (P nma, No.…”
Section: Introductionmentioning
confidence: 99%
“…respectively which with doping with small radii elements such as B, N or C have T C 's enhanced to 7.8 K for Nb 5 Si 3 and 15.3 K [6] for Nb 5 Ge 3 [7]. In this case, the superconducting properties are related to a high temperature phase (with a prototype Mn 5 Si 3 with hexagonal symmetry) that is stabilized by the interstitial doping mentioned previously.…”
mentioning
confidence: 84%
“…Although physical properties of many Ti 5 Ga 4 -type compounds are studied [1][2][3][4], the superconductivity is reported only in several compounds [5][6][7][8][9] [5] with the critical temperature T c = 9.3 K, and by increasing the oxygen concentration, T c progressively increases to 10.5 K. In this case, the oxygen addition leads to the shrinkage of c and the expansion of a, which is regarded as the enhancement of one-dimensionality of Nb2 6 and Nb1 atomic chains. The temperature dependence of specific heat of Nb 5 Ir 3 O cannot be reproduced by a single exponential temperature dependence, but explained by a two-gap model [5].…”
Section: Introductionmentioning
confidence: 99%